STUDI VARIABILITAS PARAMETER GARIS EMISI H-ALPHA BINTANG II AQUARII - Zannata Ramadhan, Taufieq
? Aquarii star is a binary star located in constellation of Aquarius. It exhibits a double peak emission line with significant variation. This emission caused by envelope surrounding the primary star. As a binary star, ? Aquarii consists of a primary and a secondary component. The primary star is classified as a B1 emission type star with a luminosity class of III-V. It has a mass of approximately 11 M?, a radius of around 6.1 R?, and an effective temperature ranging from 24000 to 25000 K. The secondary star is an A or F type star with a mass under 1.4 M?. It is a white dwarf star that orbits the primary star with a period approximately 84 days. The orbital plane is observed in inclination of 50°-75°. The two stars are separated by a distance of 200 R? from each other. The spectrum data of ? Aquarii used for this research spans from 2004 to 2024 and is retrieved from BeSS database. The IRAF (Image Reduction and Analysis Facility) software is employed to process the data. The processed data then used to determine various emission line parameters within the H? wavelength range. These parameters include V/R, E/C, FWHM, equivalent width, and peak emission separation distance. The results indicate that V/R variation ranges from 0.75-2.82. This variation may be caused by inhomogenous density gradients in the envelope known as one-armed density waves. Additionally, the E/C parameter shows a positive trend with equivalent width, increasing until 2024. This suggests an increase in envelope activity, as was observed around 40 years ago. The FWHM initially follows a similar data pattern as the EW until 2016, after which it experiences a decrease until 2024. Lastly, the data on the separation of V and R peaks indicates envelope expansion.